Pd2Ga-based colloids as highly active catalysts for the hydrogenation of CO2 to methanol - Garcia Trenco, A; White, E; Regoutz, A; Payne, D; Shaffer, M; Williams, C (American Chemical Society, 2016)
Colloidal Pd2Ga-based catalysts are shown to catalyse efficiently the hydrogenation of CO2 to methanol. The catalysts are produced by the simple thermal decomposition of Pd(II) acetate in the presence of Ga(III) stearate, which leads to Pd0 nanoparticles (ca. 3 nm), and the subsequent Pd-mediated reduction of Ga(III) species at temperatures ranging 210-290 C. The resulting colloidal Pd2Ga-based catalysts are applied in the liquid phase hydrogenation of carbon dioxide to methanol at high pressure (50 bar). The obtained intrinsic activity is up to 2-fold higher than that obtained for the commercial Cu-ZnO-Al2O3 (60.3 and 37.2 .10-9molMeOH.m-2.s-1), and 4-fold higher on a Cu or Pd molar basis (3330 and 910 μmol.mmolPd or Cu-1.h-1). Detailed characterisation (HR-TEM, STEM/EDX, XPS and XRD) indicates that the catalyst contain Pd2Ga nanoparticles, of average diameters 5-6 nm, associated with a network of amorphous Ga2O3 species. The proportion of this surface Ga2O3 can be easily tuned by adjusting the molar ratio of the Pd:Ga precursors. A good correlation was found between the intrinsic activity and the content of Ga2O3 on the surface of the Pd2Ga nanoparticles (XPS), suggesting that methanol is formed by a bifunctional mechanism involving both phases. The increase in the reaction temperature (190-240 C) leads to a gradual decrease in methanol selectivity from 60 to 40%, whilst an optimum methanol production rate was found at 210 C. Interestingly, unlike the conventional Cu-ZnO-Al2O3, which experienced approximately 50% activity loss over 25 h time-on-stream, the Pd2Ga-based catalysts maintain activity over this time frame. Indeed, characterisation of the Pd/Ga mixture post-catalysis revealed no ripening of the nanoparticles or changes in the phases initially present.